THE INCREASING DESIRES FOR IDENTITY IN UZBEKISTAN DURING THE PERESTRACTION YEARS - Hotamov Abduvohid Bobokhonovich (American Journals Publishing, 2025)
This article analyzes the intensification of the desire for self-awareness in Uzbekistan in the second half of the 1980s, during the period of perestroika and transparency policies. The processes of restoring historical truth, rediscovering national heroes, granting the Uzbek language the status of the state language, and restoring national culture and traditions are highlighted. This period is also considered as a stage when the first steps towards independence were taken, and the factors that led to the awakening of national consciousness are analyzed.
Keywords: Perestroika, transparency, national consciousness, self-awareness, historical justice, victims of repression, national heroes, state language, national culture, independence movement.